Clinicoepidemiological Profile of Agricultural Work Related Injuries in Rural Agrarian Community of Nepal: A Cross Sectional Study - Parajuli, Surya Bahadur; KC, Heera; Shah, Bikki; Parajuli, Hom Bahadur; Yadav, Binod Kumar (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Injuries have a significant proportion in the global burden of diseases and are in increasing trend. Nepal being an agrarian country had frequent reporting of injuries among rural communities whose major occupation is agriculture. So, we had this study with the objective to assess clinico epidemiological profile of agricultural work related injuries in the rural agrarian community of Nepal. Methods A community based cross sectional study was conducted among 362 farmers of rural agrarian communities of Budhiganga Rural Municipality of Nepal from 20 December 2022 to 20 June 2023 after getting ethical clearance from institutional review committee (IRC-PA 254/2022). A specially designed pro forma was used to collect data through convenient sampling techniques. Collected data was entered in Microsoft Excel and analyzed by SPSS version 23. Results The annual prevalence of agricultural work related injury was 48.6%. The most common primary causes were Sickle cut injury 43(24.4%), followed by Oxen/Cow hit injury 33 (18.8%), Traditional Plough cut injury 15 (8.5%), Spade cut injury 15 (8.5%) etc. Injury typically occurs in lower extremities 71 (40.3%). Among them 102 (58%), 82 (46.6%), 28 (15.9%) and 147 (83.5%) had a disability, bedridden, hospitalized and received some sort of treatment. Twenty two (12.5%), 36 (20.5%) and 32 (18.2%) reported stress, self reported decreased vision and self reported hearing loss at the time of injury respectively. Only 9 (5.1%) had used personal protective equipment (PPE) during agricultural work and about 36 (20.5%) had helping hands at the time of injury. Conclusions About half of farmers experienced agricultural work related injury with significant days of disability from daily activities and regular work. Use of personal protective equipment during work is miserable.